2006
DOI: 10.1002/bit.20962
|View full text |Cite
|
Sign up to set email alerts
|

High growth rate and substrate exhaustion results in rapid cell death and lysis in the thermophilic bacterium Geobacillus thermoleovorans

Abstract: Batch cultures of the thermophilic bacterium Geobacillus thermoleovorans T80 attained extremely high-specific glucose utilization rates leading to high specific growth rates, followed by extensive cell death and lysis with the onset of substrate exhaustion. The dramatic decrease in live cell numbers, as determined by flow cytometry, was accompanied by the release of soluble protein. Once the growth phase reached the point of commitment to lysis created by the impending exhaustion of substrate, the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Geobacillus , are soil inhabitants that have been reported to be the most abundant and/or dominant active group of bacteria in certain ecosystems (Felske et al ., ; Rahman et al ., ; Janssen, ), studies on functional – physiological and ecological – roles, in particular on nitrogen transformations, of these and other thermophilic organisms in both hot as cold environments are virtually nonexistent. Apart from a number of earlier reports on phenotypic denitrification and denitrification enzymes in Geobacillus (Garcia, ; Ho et al ., ; Manachini et al ., ; Nazina et al ., ), in‐depth research on thermophilic denitrifying bacteria has only been started recently (Pavlostathis et al ., ; Mishima et al ., ; Nara et al ., ; Fukuda et al ., ; Matsumoto et al ., ; Salomonsson et al ., ; Jung et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Geobacillus , are soil inhabitants that have been reported to be the most abundant and/or dominant active group of bacteria in certain ecosystems (Felske et al ., ; Rahman et al ., ; Janssen, ), studies on functional – physiological and ecological – roles, in particular on nitrogen transformations, of these and other thermophilic organisms in both hot as cold environments are virtually nonexistent. Apart from a number of earlier reports on phenotypic denitrification and denitrification enzymes in Geobacillus (Garcia, ; Ho et al ., ; Manachini et al ., ; Nazina et al ., ), in‐depth research on thermophilic denitrifying bacteria has only been started recently (Pavlostathis et al ., ; Mishima et al ., ; Nara et al ., ; Fukuda et al ., ; Matsumoto et al ., ; Salomonsson et al ., ; Jung et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…These metabolic capabilities of geobacilli suggest that they may have important biotechnological applications, both in the industrial and environmental fields (Hasan et al. 2006; Pavlostathis et al. 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Feitkenhauer et al (2001Feitkenhauer et al ( , 2003 had revealed the ability of Geobacillus thermoleovorans on phenol degradation. These metabolic capabilities of geobacilli suggest that they may have important biotechnological applications, both in the industrial and environmental fields (Hasan et al 2006;Pavlostathis et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is an alternative process for respiration used by bacteria under low oxygen conditions, through which they can reduce nitrate and/or nitrite to dinitrogen gas through the production of the intermediates nitric oxide and nitrous oxide [1]. In recent studies, the thermophilic bacterium Geobacillus thermoleovorans was shown to reduce nitrate to nitrogen gas, indicating the presence of a denitrification pathway [2]. The first catalytic step of this pathway can be achieved by two alternative enzymes: a membrane-bound or periplasmic-bound reductase (NAR and NAP, respectively).…”
Section: Introductionmentioning
confidence: 99%